Financial dependence and the adoption of the internet by non-profit organisations: The Portuguese case - Macedo, Isabel Maria (2001)
Despite the increasing popularity and potential associated with the use of Internet, nonprofit organisations are not adopting this new information technology with the same speed other sectors like business, Governments and universities do. Considering that the dependence from non-profit organisations on financial resources, can be related to a particular organisational profile, which is likely to influence the adoption of Internet by non-profit organisations, therefore, this paper attempts to analyse whether financial dependence influences or not the adoption of Internet, as well as, the perceived benefits and barriers associated with its use in a Portuguese sample of non-profit organisations.